SIMULASI MONTE CARLO UNTUK EVALUASI ANODE HEEL EFFECT PADA PESAWAT SINAR-X MENGGUNAKAN PAKET PROGRAM EGSnrc - Ramantisan, Sanggam; Anam, Choirul; Priyono, Priyono (BULETIN FISIKA; Vol 13 No 1 (2012): BULETIN FISIKA)
This study aimed to evaluate the anode heel effect on the x-ray machine for the variation of angle of anode target and tube potential. The research was conducted using Monte Carlo simulations with the EGSnrc package. The x ray was designed by BEAMnrc, whereas the phase space file was analyzed by BEAMDP. The x ray unit was designed by using Tungsten material in anoda structure. Total filtration that used was equivalent with 2,5 mm Aluminium. From the simulation found that the anode heel effect occurs only on an axis parallel to the axis x-ray tube, i.e. fluence of radiation on the cathode side is greater than the anode side. Provided that a larger angle of target will decrease the anode heel effect. Anode heel effect for angle variation on the voltage 80 kV were 17,25% (5 0 ), 15,65% (7,5 0 ), 14,65% (10 0 ), 6,96% (12,5 0 ), and 3,14% (15 0 ) respectively. As for variations in tube voltage was obtained that the anode heel effect is relatively small. Anode heel effect for the tube voltage variation on the tube anode angle 15 0 were 1.99% (40 kV), 2.20% (60 kV), 3.14 (80 kV), and 3.81% (100 kV) respectively.